Mass Spectrometry Imaging Differentiates Chromophobe Renal Cell Carcinoma and Renal Oncocytoma with High Accuracy - Kriegsmann, Mark; Casadonte, Rita; Maurer, Nadine; Stoehr, Christine; Erlmeier, Franziska; Moch, Holger; Junker, Klaus; Zgorzelski, Christiane; Weichert, Wilko; Schwamborn, Kristina; Deininger, Soeren-Oliver; Gaida, Matthias; et al. (Journal of Cancer, 2020)
Background: While subtyping of the majority of malignant chromophobe renal cell carcinoma (cRCC) and benign renal oncocytoma (rO) is possible on morphology alone, additional histochemical, immunohistochemical or molecular investigations are required in a subset of cases. As currently used histochemical and immunohistological stains as well as genetic aberrations show considerable overlap in both tumors, additional techniques are required for differential diagnostics. Mass spectrometry imaging (MSI) combining the detection of multiple peptides with information about their localization in tissue may be a suitable technology to overcome this diagnostic challenge.
CRIS-Team WoS Importer:2020-09-11